Multiple mini interviews: revealing similarities across institutions - Griffin, Barbara (BMC Med Educ, 2018)
BACKGROUND: Across the globe multiple mini interviews (MMIs) have rapidly replaced the use of panel interviews in the selection of medical students and other health professionals. MMIs typically demonstrate better reliability and validity than panel interviews but there is limited research on whether these different types of interview process measure the same or different constructs. Our research aims to ascertain if MMIs are multidimensional or unidimensional, and whether MMIs conducted at different institutions assess the same or different constructs to each other or to panel interviews. METHODS: Participants were applicants to medical degrees who were shortlisted for interviews at three different institutions in 2013 (n = 165) and 2014 (n = 128). Two institutions used a bespoke MMI developed independently from each other and the third used a panel interview. Stations scores and overall (mean) interview scores were examined. RESULTS: Exploratory principal components analysis and confirmatory factor analysis showed similar results in both years’ data, supporting a unidimensional model. The two overall MMI scores were more strongly correlated to each other (r = .56 and .64 in 2013 and 2014 respectively) than either were to the panel interview scores (r = .07 and .15 in 2013; .39 and .48 in 2014). CONCLUSIONS: It appears that both MMIs panel interviews tap a single latent construct, but not the same construct. We suggest that the MMI methodology might allow the measurement of an emergent construct such as adaptability. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12909-018-1298-8) contains supplementary material, which is available to authorized users.